The effects of COVID-19 vaccines on economic activity - Pragyan Deb; Davide Furceri; Daniel Jiménez; Siddharth Kothari; Jonathan David Ostry; Nour Tawk (Swiss Journal of Economics and Statistics, 2022)
This paper empirically examines the economic effects of COVID-19 vaccine rollouts using a cross-country daily database of vaccinations and high-frequency indicators of economic activity - nitrogen dioxide (NO2) emissions, carbon monoxide (CO) emissions, and Google mobility indices - for a sample of 46 countries over the period December 16, 2020 to June 20, 2021. Using surprises in vaccines administered, we find that an unexpected increase in vaccination per capita is associated with a significant increase in economic activity. We also find evidence for nonlinear effects of vaccines, with the marginal economic benefits being larger when vaccination rates are higher. Country-specific conditions play an important role, with lower economic gains if strict containment measures are in place or if the country is experiencing a severe outbreak. Finally, the results provide evidence of spillovers across borders, highlighting the importance of equitable access to vaccines across nations.
Keywords: C31; C33; E65; O50; F4; 330; COVID-19; Pandemics; Vaccinations; Containment measures